In Situ Thermal Decomposition of Potassium Borohydride for Borophene Synthesis and Its Application in a High-Performance Non-Volatile Memory Device - Qian Tian; Xinchao Liang; Maoping Xu; Yi Liu; Qilong Wu; Guoan Tai (Nanomaterials)
Borophene, a revolutionary two-dimensional (2D) material with exceptional electrical, physical, and chemical properties, holds great promise for high-performance, highly integrated information storage systems. However, its metallic nature and structural instability have significantly limited its practical applications. To address these challenges, hydrogenated borophene has emerged as an ideal alternative, offering enhanced stability and semiconducting properties. In this study, we report a novel and scalable method for synthesizing hydrogenated borophene via the in situ thermal decomposition of potassium borohydride in a substrate-free environment. This approach enables the production of borophene with outstanding crystallinity, uniformity, and continuity, representing a significant advancement in borophene fabrication techniques. Furthermore, the hydrogenated borophene-based non-volatile memory device we developed exhibits a high ON/OFF-current ratio exceeding 105, a low operating voltage of 2 V, and excellent long-term cycling stability. These groundbreaking results demonstrate the immense potential of 2D borophene-based materials in next-generation high-performance information storage devices.